Metabolic disorders in kidney stone disease in children - Kusz, Monika; Alzubedi, Adam; Polski, Paweł; Pawluczuk, Paulina; Maślak, Agnieszka (Journal of Education, Health and Sport, 2020)
Urolithiasis is not a rare disorder in children. Its etiology, incidence and localization vary by geographic region. It is an increasing problem, especially in developing countries. Metabolic abnormalities have been claimed to play a significant role in the kidney stone disease. Most of the studies confirmed that hypercalciuria, hypocitraturia are the most commonly identified metabolic disorder in children with urolithiasis. It is important to evaluate them to modify and prevent the stone recurrence.